Moderating effect of environmental turbulence on firm’s technological innovation capabilities (TIC) and business performance in the automotive industry in Malaysia: A conceptual framework - Faridah, Taju Rahim; Yuserrie, Zainuddin (EDP Sciences, 2017)
The dimensions that constitute the technological innovation capabilities (TIC) can be a source to improve business performance. Based on the resource-based view and contingency theory, this paper tries to propose a conceptual model to further understand the moderating role of environmental turbulence in effecting of the firm’s TIC on firm’s business performance in the automotive industry in Malaysia. This paper then developed into concrete research hypotheses for future studies. The conceptual model will serve to guide further research in the area, which can be expected to contribute in the development of automotive industry in Malaysia. Empirical testing of this proposed model is expected in future study using survey instrument.